Market responses in Indonesia to the Russia─Ukraine War Announcment: Evidence from LQ45 Companies ( 2020–2024) - Wicaksana, Raihan Wira; Sari, Rida Perwita (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to examine whether the Indonesian capital market experienced significant differences in average abnormal return (AAR) and average trading volume activity (ATVA) before and after the announcement of the Russia–Ukraine war. Methodology: The research employs an event study approach involving 24 companies consistently listed in the LQ45 index during the 2020–2024 period. Abnormal returns were calculated using the Market-Adjusted Return model, while trading volume activity was measured as the ratio of traded shares to outstanding shares. Due to data non-normality, the Wilcoxon Signed Rank Test was applied for hypothesis testing. Results: The results indicate that the announcement of the Russia–Ukraine war did not significantly affect average abnormal returns, but it had a significant impact on trading volume activity, reflecting changes in investor behavior. Novelty: This study extends the event window to a four-year period, offering a long-term perspective on capital market responses to geopolitical shocks. Findings: Investors tended to reduce trading activity following the war announcement, signaling increased caution and declining market liquidity. Originality: The originality of this study lies in its long-horizon event study design focusing on Indonesia’s leading stocks. Conclusions: Geopolitical events may not immediately alter stock returns but can significantly influence market liquidity and trading behavior. Type of Paper: Empirical Quantitative Research Paper.